Causation in Medical Malpractice: Evaluating Conditio Sine Qua Non, Adequate Causation, and Objective Imputation in Indonesian Court Decisions - Muabuay, James Wilson; Panggabean, Mompang Lycurgus; Siregar, Rospita Adelina (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This study examines the application of causation theories in medical malpractice cases, focusing on the complex intersection between medical uncertainty and legal certainty. Within the inherently multi-causal nature of clinical practice, establishing a definitive causal link between a physician's omission and a patient's death remains a significant judicial challenge in Indonesia.Purposes of the Research: This research aims to evaluate the consistency of judicial reasoning in applying causation theories through an in-depth analysis of the District Court of Denpasar Decision No. 126/Pid.Sus/2011/PN.Dps. Furthermore, it seeks to identify whether the court's approach aligns with modern normative attribution standards in criminal law.Methods of the Research: Employing a normative legal research method with statute, case, and conceptual approaches, the study compares conditio sine qua non, adequate causation, and objective imputation.Findings of the Research: Findings reveal a “methodological shift” in judicial reasoning, moving from rigid factual analysis towards elements of adequate causation and objective imputation. However, a critical flaw identified is the court's failure to distinguish between “inherent medical risks” and “negligent risks”. The novelty lies in exposing the inconsistent application of these theories, leading to legal unpredictability. The study concludes that Indonesian courts require a more robust normative framework, particularly the integration of objective imputation, to ensure criminal liability in medical malpractice is assessed based on professional standards, not just fatal outcomes.